Is anterior oblique view alone in surgical position sufficient for preoperative sentinel lymph node mapping in breast cancer? A quantitative comparative analysis with conventional views - (:unkn) unknown (IMPRIMATUR PUBLICATIONS, 2009)
Purpose: Since the anterior projection alone has several limitations in the conventional preoperative sentinel lymph node (SLN) mapping, multiple projections including anterior oblique (AO) view are preferred. There are many AO acquisition techniques described in the literature but none of them creates an image which fully reflects the surgical perspective. We aimed to compare the AO view in the surgical position with the conventional projections according to quantitative parameters. Patients and methods: Sixty female breast cancer patients entered the study. Two hours after the radiotracer injection, preoperative AN mapping at anterior lateral and 35 degrees AO projections in surgical position was performed For each projection, mapping success rate (MSR), the mean number of SLNs, lymphatic channel visualization rate, image contrast and distance measurements between each SLN and between the SLNs and the injection site were recorded. Results: The best MSR and image contrast for the first and the consecutive axillary SLNs were found at the AO projection. The longest distance between the injection site and the SLNs and between the two SLNs were observed at the AO views. Although the AO view, gave the best results for intramammary SLNs the difference was not statistically significant from the anterior view. Conclusion: The 35 degrees AO view in the surgical position was superior to the anterior and lateral projections. Therefore, the simple 4-min AO view in the surgical position may entirely reflect the surgeon's perspective and could be used safely alone in the preoperative lymphatic mapping for breast cancer patients.
Keywords: acquisition projection; breast cancer; lymphoscintigraphy; sentinel lymph node; surgical position; UPRIGHT POSITION; LYMPHOSCINTIGRAPHY; BIOPSY; LOCALIZATION; IDENTIFICATION; INJECTION; FAILURE; PREDICT; NUMBER; CT